La integración del mercado eleéctrico de los países nórdicos: - NORD POOL - lecciones para otros mercados (2006)
This article describes the process of integration of the electrical market of the Nord Pool, besides to establish some reflections on this experience, which can be considered by regions that are in the same process as the case of the Andean Community of Nations - CAN. Initially this paper makes reference to the theoretical elements that base the exchange of goods and services and the economic principles that justify the integration of markets and finally are concentrate abaut the case and some results of the Nord Pool.